Etika Penggunaan Media Social dalam Perspektif Hadis Studi Tentang Privasi dan Tanggung Jawab Social - Zaid Almubarok Simangunsong; Ferizal Ferizal (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the ethics of social media use from the perspective of hadith and verses of the Qur'an with a focus on privacy and social responsibility. Social media, as a dominant communication tool, is often misused, resulting in privacy violations, the spread of inaccurate information, and other negative impacts. This study uses a literature approach to authentic hadiths and interpretations of verses of the Qur'an. The results of the study show that Islam prohibits the actions of tajasuss (spying) and ghibah (backbiting), as emphasized in the hadith: